PENGARUH PEMBERIAN JUS PEPAYA (CARICA PAPAYA) TERHADAP PENURUNAN TEKANAN DARAH PENDERITA HIPERTENSI DI KELURAHAN PASIR AMPO TAHUN 2021 - Agustina, Riska; Chasanah, Siti Cholifah S.; Faridah, Ida (Nusantara Hasana Journal, 2022)
High blood pressure isa disease that is often found in adults. Hypertension is a problem for health and one of the risk factors that occurs in the community and is difficult for someone to realize because the disease doesn’t have specific symptoms. Some people often underestimate hypertension and some people believe that hypertension is not a serious disease and doesn’t require special treatment. The purpose of this study was to determine the effect of drinking papaya juice (Carica Papata) on reducing blood pressure in Pasir Ampo Village in 2021. The type of research use in this study is a quantitative study with a quasi experimental design, the sampel in this study were residents of the pasir ampo village as many 30 respondents with treatment group of 15 respondents an a control group of 15 respondents. The measuring instrument use aresphygmomanometer, stetoskop and observation sheet. Sampling was done by purposive sampling technique. The data analysis technique used is univariate and bivariate. The results showed that drinking papaya juice and average systolic value of treatment group was 134,66/84,66 mmHg and with an average blood loss of 10 mmHg to 20 mmHg with p-value (0,001) < ɑ (0,05) so Ho is rejected, meaning that there is an effect of giving papaya juice (Carica Papaya) to decrease blood pressure.  The results of this study can be concluded that there effect of giving papaya juice (Carica Papaya) to reducing blood pressure of hypertension sufferes in the Pasir Ampo Village. It’s recommended for people with hypertension to drink papaya juice as an alternative non-pharmacological therapy.